Business Analysis of Pomade Rambutan Leaf Extract with Apple Aroma Anti-Gray Hair and Multipurpose as a Green Economy Alternative - Dewi Oryza Sativa, Rima; Widiatmanta, Jeka; Febrianti, Neha; Hendra Kusuma, Agung (International Journal of Science, Technology & Management, 2025)
Blitar is the city with the largest rambutan fruit commodity. The number of plants throughout the district was recorded at approximately 283,437 trees, with a productivity level of 115 kilograms per tree. Rambutan (Nephelium lappaceum) has benefits for the health of the human body in the form of cleansing kidney function, preventing heart disease. Not only in the fruit, rambutan trees also have many benefits in every part. Tjandra's research says that rambutan leaves and skin contain compounds of tannins, polyphenols and saponins that function as a prevention of gray hair. This pomade-shaped hair styling product "HYUNG HAIR" made from rambutan leaf extract has properties including reducing hair loss, nourishing the scalp, slowing the growth of gray hair and can change the color of the pigment in the hair. The activity of making rambutan leaf extract pomade was carried out for four months, starting from Maret 2025 to Mei 2025. Product testing activities and production processes were carried out at Balitar Islamic University, as well as at one of the production houses located in the Bendo Area, Ponggok, Blitar Regency, East Java. The price we offer on "Hyung hair" Pomade is RP. 24,000, -, with the calculation of business feasibility analysis calculated through the R / C Ratio showing the number 1.24. Where the value is more than one which shows the rambutan leaf extract pomade business is feasible to run.